Germacrane sesquiterpenes from leaves of Eupatorium chinense inhibit protein tyrosine phosphatase. (1st December 2021) - Yamazaki, Hiroyuki; Tsuge, Hayato; Takahashi, Ohgi; Uchida, Ryuji
Graphic abstract: Abstract: Three new germacrane-type sesquiterpene lactones (1 –3 ) were isolated alongside seven known related congeners (4 –10 ) from the leaves of Eupatorium chinense L. (Compositae). The planar structures of 1 –3 were elucidated by their spectroscopic data, including 1D and 2D NMR spectra. The relative and absolute configurations of 1 –3 were determined using NOESY experiments and electronic circular dichroism analyses. Compounds 1, 4, 5, and 7 inhibited protein tyrosine phosphatase (PTP) 1B activity with IC50 values of 25, 11, 28, and 24 μM, respectively. Among these, compound 4 exhibited an inhibitory effect on T-cell PTP (TCPTP) with an IC50 value of 25 μM. To our knowledge, this is the first study demonstrating the PTP inhibitory activity of the germacrane sesquiterpenes. The results show that compound 4 acts as an inhibitor of both PTP1B and TCPTP.